Fracture of the Fabella: A Rare Injury in Knee Trauma - Andre Rodrigues Façanha Barreto; Francisco Abaete Chagas-Neto; Michel Daoud Crema; Mario Muller Lorenzato; Mariana Tiemi Teixeira Kobayashi; Carlos Ribeiro Monteiro; Marcello Henrique Nogueira-Barbosa (Case Reports in Radiology)
We present a case of a 21-year-old woman sustaining a traumatic [fabellar] fracture following a motor vehicle accident. The fabellar fracture was confirmed on plain films, which prompted further evaluation of the knee with ultrasound and magnetic resonance imaging to evaluate other possible associated injuries. Fracture of the fabella is a rare condition. Clinically, patients present with posterolateral knee pain, edema, and limited knee extension. Occasionally these symptoms may be very subtle, delaying the correct diagnosis and patient management.